Answer:
-12
Step-by-step explanation:
8x - 2(6 - x)
Substitute 0 for each x
8*0 - 2(6 - 0)
Solve.
0 - 2*6
0 - 12
-12
Answer:
The answer to your question is A) x = 1
Step-by-step explanation:
We know that f(x) = 2x + 3 and g(x) = -x + 6
But f(x) = g(x)
Then, 2x + 3 = - x + 6
2x + x = 6 - 3
3x = 3
x = 3/3
x = 1
The solution is circle in the graph below.
Answer:
jajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajajaja
1
The answer to this is b- 8